Fintech User Satisfaction as an Intermediary: Analysis of The Influence of Financial Literacy, Ease of Use, and Trust on User Loyalty in MSMEs - Solihati, Garin Pratiwi; Anah, Sri; Anggraini, Wahyu (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2025)
The growth of financial technology (fintech) has transformed MSME operations, particularly in accessing financial services. This study analyzes the impact of financial literacy, ease of use, and trust on fintech user satisfaction and their role as mediating variables in fostering user loyalty among MSMEs. Using a quantitative approach, data were collected via an online questionnaire from 100 SME respondents in Yogyakarta. Structural Equation Modeling-Partial Least Squares (SEM-PLS) was employed to examine the relationships between variables. The findings reveal that financial literacy, ease of use, and trust have a positive and significant influence on user satisfaction. Moreover, user satisfaction has a positive and significant mediating effect on the relationship between financial literacy, ease of use, trust, and user loyalty. This indicates that improving these factors enhances user satisfaction, which subsequently strengthens user loyalty to fintech platforms. This study underscores practical implications, urging fintech providers to enhance accessibility, security, and transparency to boost user satisfaction. It also recommends that governments and educational institutions implement inclusive financial literacy programs to encourage broader fintech adoption among MSMEs. The study contributes to technology adoption literature by emphasizing user satisfaction as a critical mediator in establishing long-term loyalty. Future research should explore broader regions, larger sample sizes, and additional variables such as digital competence for deeper insights into fintech adoption dynamics.